Alien Invasion: The Case of the Western Conifer-Seed Bug (Heteroptera: Coreidae) in Chile, Overreaction, and Misidentifications - Faundez, Eduardo; Carvajal, Mariam A.; Villablanca, Javier (My University, 2020)
Leptoglossus occidentalis (Heidemann) is an invasive species introduced in Europe, Asia, and most recently South America. In the present study, we report the overreaction situation caused by this bug in Chile, as it has been confused with kissing bugs (Reduviidae: Triatominae), Chagas' disease vectors. During 2018 and first months of 2019, we received 74 alleged cases of kissing bugs to confirm identification. From these, a total of 63 were identified as L. occidentalis, representing a 85% of the total denounces. Additionally, the first bite case in a human is described. The situation caused by L. occidentalis in Chile is discussed, and an illustrated table is provided to correctly identify this species and tell it apart from Triatomines. It is concluded that L. occidentalis is well established in Chile, and it is necessary to educate the population on recognition of the bug and to avoid overreaction as the species can inflict painful bites, but not transmit any disease.
Keywords: hemiptera; coreinae; triatominae; bite; identification